Free-Living Ice-Nucleating Active Bacteria from High Mountain Lake Habitats - MUNTI YUHANA; KURT HANSELMANN (Microbiology Indonesia, 2008)
We collected the culturable heterotrophic bacteria from oligotrophic high mountain lake habitats and tested their capability to induce ice formation. Direct plating was carried out using low-nutrient medium at a temperature of between 3 and 4°C. As many as 84 isolates were recovered from glacial ice and natural biofilm growing on granite rocks surface. Six out of 84 isolates were capable of expressing the ice-nucleation phenotype. After autoclaving the cell suspension at 121°C for 15 min, isolate J78 was still able to retain the ability for ice formation. Heat-stable ice nuclei produced by ice-nucleating active bacteria have potential applications in biotechnology. Characterization of INA bacteria was performed employing live-dead Gram staining and molecular methods. Universal primers for Bacteria (S-D-Bact-0008-b-S-20 and S-D-Bact-1524-a-A-18) were used for PCR to amplify almost the full length of the 16S rRNA genes of selected INA isolates. Restriction fragment length polymorphism analysis resulted in 2 unique patterns, as represented by J43 and J83, respectively. Based on DNA sequencing of 16S rRNA gene, isolate J43 (GeneBank accession no. AJ864852) was closely related to Pseudomonas mephitica (99.2% sequence similarity) and Janthinobacterium lividum (99% similarity), whereas isolate J83 (GeneBank accession no. AJ864859) showed 100% sequence identity to Pseudomonas fluorescens.